1993
DOI: 10.1016/0014-5793(93)81209-i
|View full text |Cite
|
Sign up to set email alerts
|

GTPγS and phorbol ester act synergistically to stimulate both Ca2+‐independent secretion and phospholipase D activity in permeabilized human platelets

Abstract: We have tested the hypothesis that phospholipase D (PLD) is the effector of the unidentified G protein (GE) mediating Ca"-independent exocytosis in platelets. Although GTPyS, and to a lesser extent phorbol 12-myristate 13-acetate (PMA), caused some secretion of 5-HT from electropermeabilized human platelets in the effective absence of Ca*' (pCa > 9) these stimuli had much more potent synergistic effects when added together. In all cases, secretion of 5-HT was closely correlated to the stimulus-induced formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 28 publications
2
34
1
Order By: Relevance
“…Comparison of the initial part of the present study with previous work using electropermeabilized platelets [5,8,9,23,26] suggested that similar regulatory mechanisms were operating in the two permeabilized platelet preparations, but with some quantitative differences. The sensitivities of dense-granule secretion to Ca# + in the two preparations were comparable and, in both, addition of PMA or GTP[S] enhanced Ca# + responsiveness, the latter more effectively than the former.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Comparison of the initial part of the present study with previous work using electropermeabilized platelets [5,8,9,23,26] suggested that similar regulatory mechanisms were operating in the two permeabilized platelet preparations, but with some quantitative differences. The sensitivities of dense-granule secretion to Ca# + in the two preparations were comparable and, in both, addition of PMA or GTP[S] enhanced Ca# + responsiveness, the latter more effectively than the former.…”
Section: Discussionsupporting
confidence: 67%
“…Our observation that GTP[S] stimulated secretion in the presence of 10-100 nM PMA, which induces a marked to maximal phosphorylation of pleckstrin, confirms our previous conclusion [5][6][7][8] that GTP[S] acts by mechanisms additional to stimulation of the phospholipase C-PKC axis. We have previously provided evidence that GTP[S] may exert some of its effects by stimulating phospholipase D activity [8,9], but the present study suggests an additional action. Thus GTP [S] induced major changes in the ultrastructure of SLO-permeabilized platelets in the absence of Ca# + or of any activation of PKC.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…In contrast to FIPI, ethanol and especially 1-butanol displayed distinct inhibitory effects on PAR-1 and PAR-4 activating peptide-induced Ca 2+ mobilization, dense granule secretion and aggregation of human platelets indicating that prior studies that rely on PLD inhibition by primary alcohols must be re-evaluated. In the nineties Coorssen and Haslam proposed that PLD is important for human platelet secretion by using ethanol to block PLD mediated effects on degranulation [45]. In a recent study it was shown that 1-butanol abrogated platelet aggregation by PAR-1 but not PAR-4 activating peptide [46].…”
Section: Discussionmentioning
confidence: 99%
“…The ras-transformed cell lines used here were obtained from independent transfections and have been described previously [6,22], or were freshly generated using an LTR-driven vector (LP14-8) or simian virus 40 ), and butan-1-ol was from Merck. Bisindolylmaleimide was purchased from Calbiochem.…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%